Depth resolved near-surface residual stresses in γ-based TiAl before and after high-temperature exposure. (May 2017) - Paul, J.D.H.; Oehring, M.; Appel, F.; Pyczak, F.
Abstract: The aim of this study was to gain an insight into the development of near-surface stress, which has been proposed to play a role in environmental embrittlement, as a function of depth after exposure. Investigations were performed, using both energy and angle-dispersive X-ray diffraction, to determine the residual stress as a function of depth for flat specimens made from two γ-based TiAl alloys in as-polished and exposed (700 °C/1 h/air) conditions. It has been found that large compressive stresses are present at the surface of as-polished specimens due to sub-surface deformation that remains despite careful grinding/polishing. After exposure the compressive residual stresses at depths below 0.6 μm are significantly reduced, probably due to the annealing out of deformation induced defects, but remain compressive in nature. However, within 0.6 μm from the outer surface, tensile stresses were present and reached a maximum of around +350 MPa at 0.15 μm depth. The extent to which the development of superficial tensile residual stress and reduced deeper compressive stress contribute to embrittlement remains unclear. Highlights: The residual stress has been measured before and after high-temperature exposure. Before exposure there is a high compressive stress at the surface and diminishes with depth. After exposure a tensile stress is developed in the outer 0.6 μm surface layer.